If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 4 + 2j Solving 6 = 4 + 2j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2j' to each side of the equation. 6 + -2j = 4 + 2j + -2j Combine like terms: 2j + -2j = 0 6 + -2j = 4 + 0 6 + -2j = 4 Add '-6' to each side of the equation. 6 + -6 + -2j = 4 + -6 Combine like terms: 6 + -6 = 0 0 + -2j = 4 + -6 -2j = 4 + -6 Combine like terms: 4 + -6 = -2 -2j = -2 Divide each side by '-2'. j = 1 Simplifying j = 1
| -26=-8y+6(y-5) | | 13c-9c=16 | | -23-38= | | -7x-2x-11=-13 | | 10x+5+6x+5=90 | | z=y^2-x^2 | | 13-42=3(x-1)-5 | | f(x)=3-11 | | 5/8x=5/48 | | -2(x-5)=3x-10 | | 0.2*20=m | | 36mn-4m= | | 16h=19 | | n-3.2=56 | | -63-(-4)= | | 2(w+3)-7w=11 | | lnx=x^3+8 | | (y^2+2xy)-(x^2)dx=0 | | 0.11y=-9 | | 1.5m=11 | | 1.3=8.02 | | 4x+2-3x=10 | | -27=3(x-5)-5x | | -6+13x+-1x^2+-2x^3=0 | | y=-10-1 | | 75=d+15 | | 3x^2-4x+1024=0 | | -15n-20=12n-20 | | 4(8x-7)-7(6-7x)= | | 13x+30=3x+160 | | 72/(-9) | | 4z=-56 |